Pengembangan Media Pembelajaran Digital Android Vinomath Berbasis Contextual Teaching Learning Pada Materi Perbandingan Trigonometri - Jannah, Vani Mar'atul; Farid Gunadi; Luthfiyati Nurafifah (Jurnal PEKA (Pendidikan Matematika), 2026)
The lack of understanding of the concept of trigonometric comparisons in daily life and the lack of student interest in the material became obstacles in learning mathematics, so a contextual approach is needed to link the concept of trigonometric comparisons with real situations and the use of interactive learning media. This study aims to determine the feasibility, practicality and effectiveness of Android Vinomath digital learning media based on Contextual Teaching Learning on trigonometric comparison material. This research uses the Research and Development (R&D) method with the 4D development model (Define, Design, Development, and Disseminate). Participants in this study were 10th-grade students, teachers and the vice principal. Data collection used interviews, tests, and surveys. Data analysis used qualitative and quantitative methods, appropriate to the stages. The trial results show that the Vinomath media is deemed worthy of being reviewed through validation by theoretical experts and practitioners. This media was also considered practical based on student responses and teacher observation results and was proven effective through test results and student learning interest questionnaires. The use of Vinomath media optimizes students' understanding of concepts and interest in studying trigonometric comparison material.